Wykup własnych akcji jako element polityki inwestycyjnej w spółce - Kołosowska, Bożena (Share Repurchase as an element of Corporation Investment Policy, 2006)
Share repurchase is becoming a new method of acquiring new capital. The article presents several different motives for performing such operations. First of all, share repurchase programmes are a good way for cash distribution among shareholders and re-allocation of capital from mature or declining sectors of the economy to more productive areas. Polish law permits Polish companies to buyback their stock. Buyback programmes can be used to boost earnings per share, to adjust debt-to-equity ratios or to change share ownership structure of a company. Companies announce buyback when their stock is "undervalued" by the market. Share repurchase may also protect a firm against outside takeovers. Among the most important advantages of this operations is expected the increase of company's shares value
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 326-336